"I wouldn't imagine having to go through all this and still be the same person. No way": structure, reflexivity and international students. (December 2017) - Matthews, Blair
International students at universities away from their home context experience a significant change to the way they engage with the world, as they think, reflect and act in response to the new context. Drawing on Archer's concept of reflexivity (2003; 2007; 2012), this paper demonstrates that international students are compelled into reflexive deliberation, which precipitates a change in agency. This paper provides empirical evidence of specific generative mechanisms of the international student experience, which contribute to the conditioning of agency.